The European commission's discretion as to the adoption of Article 9 commitment decisions: Lessons from Alrosa - Piero Cavicchi (Europa-Kolleg Hamburg, Institute for European Integration, 2011)
Introduced by Article 9 of Regulation 1/2003, commitment decisions represent a tool - alternative to Article 7 infringement decisions - available to the European Commission in order to ensure an effective implementation of the EU antitrust rules. Over the last few years there has been an increased recourse to commitment decisions in antitrust cases. This paper explores the reasons for the apparent success of this new instrument and anticipates the consequences of the recent Alrosa judgment rendered by the European Court of Justice, which limits the judicial review of commitment decisions to the manifest incorrectness of the Commission's assessment. The paper concludes that, in light of the extent of the Commission's discretion as to the adoption of commitment decisions defined by the Court in Alrosa, the observed trend seems likely to continue. In particular, given the generous boundaries set by the Court to the Commission's discretionary power, hopes of avoiding system failures in commitment decisions seem actually to be pinned on the Commission's self-restraint more than on the potential for control by the Luxembourg Courts.
Keywords: 330; Article 9 of Regulation 1/2003; Article 7 of Regulation 1/2003; commitment decisions; infringement decisions; Commission's discretionary power; principle of proportionality; ECJ Alrosa judgment